Mutational insights and in silico characterization of NEK family kinases in OSCC patients from the Pakistani population - Nawab, Fouzia; Naeem, Wafa; Fatima, Sadia; Khan, Muhammad Uzair; Mehmood, Aamir; Nawab, Sadia; Khan, Ishaq; Nawaz, Haseena; Ahmad, Hilal; Khalil, Ali Talha; Khan, Ishtiaq Ahmad; Irfan, Muhammad; et al. (Frontiers in Bioinformatics, 2026)
IntroductionOral squamous cell carcinoma (OSCC) is a prevalent malignancy characterized by aggressive behavior, poor prognosis, and limited therapeutic options. Mutations in the NIMA-related kinase (NEK) family are increasingly implicated in tumorigenesis across various cancers. However, their contributions to OSCC pathogenesis remain largely unexplored.MethodsHere, we employed whole-exome sequencing (WES) of formalin-fixed paraffin-embedded (FFPE) tissue blocks from 31 OSCC tumors and 9 adjacent paired normal samples derived from patients of Khyber Pakhtunkhwa (KP), Pakistan, to systematically profile NEK gene alterations. Subsequent in-silico analyses were performed to evaluate the structural and functional consequences of the identified mutations.ResultsWe identified 46 mutations overall (78.3% (36/46) somatic, 21.7% (10/46) germline), consisting of 82.6% (38/46) non-synonymous single-nucleotide variants (SNVs), 10.9% (5/46) frameshift deletions, 2.2% (1/26) non-frameshift deletions, and 4.3% (2/46) stop-gain mutations; notably, 10.9% (5/46) represented novel variants (not reported previously). NEK1 displayed the highest mutation frequency, followed by NEK10, NEK5, NEK11, NEK2, and NEK3. ISPRED-SEQ classified 37.0% (17/46) of mutations as residing at protein-protein interaction interfaces, indicating potential functional relevance, with several mutations including NEK1p.D409Y, NEK1p.N643K, NEK9 p.H174Y, NEK10 p.R275C, and NEK10 p.E596K predicted to be deleterious and destabilizing by multiple tools, occurring at conserved residues and altering structural stability via molecular dynamics simulations. Clinically, NEK4 mutations were significantly associated with tumor site (P=0.02), NEK9 with tobacco exposure (P=0.01), and NEK10 with improved overall survival (P=0.01). Mutations including NEK11p.E347V (31/31), NEK9p.R429H (23/31), NEK10p.L513S (15/31), NEK4p.P136A (7/31), NEK5p.K255Q (6/31) and NEK1 p.E650G (5/31) were found to be recurring mutations and can be validated further in large-scale studies for biomarker applicability.ConclusionCollectively, these findings suggest NEK mutations as candidate drivers of OSCC pathogenesis, underscoring their potential as prognostic biomarkers and therapeutic targets, particularly in tobacco-associated disease.